Understanding conflict in the co-management of forests: the case of Bulungan Research Forest - Yasmi, Yurdi (2003)
The paper describes underlying causes of conflicts between local people in Bulungan Research Forest (BRF), Indonesia with coal-mining and logging companies. Results show that conflict between local people and mining companies was triggered by the fact that mining operation caused water and air pollution and soil degradation. Another cause for such a conflict was the compensatory facilities (e.g. clean water, electricity, compensation fee, etc.) provided by the companies to local people were often delayed or unsatisfactory. Local people perceived that their major problem with logging activities was the adverse impact to residual plants such as rattan, eagle wood, medical plants, etc. Not only that, logging companies do not allow local people to cut trees although only for their own uses such as for house or church. The paper concludes that there is a need for negotiation among those parties involved in conflict in such a way that negative impact can be reduced and positive impacts can be enhanced.